Epidemiology, tumour characteristics, treatment and outcomes associated with spinal nerve sheath tumours: a systematic review protocol - Erik Edström; Adrian Elmi-Terander; Victor Gabriel El-Hajj; Maria Gharios; Omar Ali Mahdi; Aman Singh; Adnan Fatfat (BMJ Open)
Introduction Nerve sheath tumours arise from both the central and peripheral nervous systems. In particular, cases of spinal or paraspinal origins are scarce and poorly covered in the literature. This systematic review aims to summarise the body of evidence regarding spinal nerve sheath tumours and assess its quality, to provide the current knowledge on epidemiology, tumour characteristics, diagnostics, treatment strategies and outcomes.Methods and analysis Databases including PubMed, Web of Science and Embase will be searched using keywords such as “spinal”, “nerve sheath”, “neurofibroma”, “schwannoma”, “neurinoma” and “neurilemoma”. The search will be limited to studies published no earlier than 2000 without language restrictions. Case reports, editorials, letters and reviews will be excluded. Reference lists of identified studies will be searched to find possible additional relevant records. Identified studies will be screened for inclusion, by one reviewer at first and then two independent ones in the next step to increase the external validity. The Rayyan platform will be used for the screening and inclusion process. Data extraction within several predetermined areas of interest will proceed. Subjects of interest include epidemiology, histopathology, radiological diagnostics, surgery, complications, non-surgical treatment alternatives, disease outcomes and predictors of outcome, and recurrence rates. On satisfactory amount of homogenous data, a meta-analysis of key outcomes such as recurrence risk or postoperative neurological improvement will be performed. This systematic review will primarily serve as a reference guide to aid in diagnosis and treatment of patients with spinal schwannomas, while also spotlighting the knowledge gaps in the literature to help guide future research initiatives.Ethics and dissemination Ethics approval is not required for the protocol or review as both are based on existing publications. For dissemination, the final manuscript will be submitted to a peer-reviewed journal.